P.117 The opinion of Canadian spine surgeons on medical assistance in dying (MAID); a cross-sectional survey of Canadian spine society (CSS) members. (June 2019) - Leck, E; Barry, S; Christie, S
Abstract : Background: On February 6, 2015, the Supreme Court of Canada struck down the Criminal Code absolute prohibition on assisted dying, and in June 2016 the new law, Bill C-14, came into effect allowing for medical assistance in dying. We sought to determine the attitudes and opinions of Canadian neurosurgeons and orthopedic spine surgeons regarding MAID. Methods: A cross-sectional survey was sent out to members of the Canadian Spine Society (CSS), which included 21 questions pertaining to opinions regarding MAID. Responses were collected between May-June 2016. Results: A total of 51 surgeons responded to the survey, comprised of a mix of spine surgeons from across the country. The majority of surgeons supported MAID (62.8%), and right of physicians to participate (82.4%). Most surgeons supported the right to conscientious objection (90.1%), but also mandatory duty to refer (49.0%). The conditions most frequently felt to be appropriate for MAID included metastatic spine tumour (76.5%), malignant intramedullary tumour (64.7%), primary malignant spine tumour (54.9%), cervical spinal cord injury with tetraplegia (49.0%) and multiple myeloma (33.3%). Conclusions: This study highlights the complex landscape that exists when discussing MAID, but also the overall support of physicians, and need for ongoing conversations, particularly with issues not addressed by the current legislation.